2022
DOI: 10.3171/2021.5.jns21949
|View full text |Cite
|
Sign up to set email alerts
|

Lateral versus vertical hemispheric disconnection for epilepsy: a systematic review and meta-analysis

Abstract: OBJECTIVE Lateral periinsular hemispherotomy (LPH) and vertical parasagittal hemispherotomy (VPH) are the most popular disconnective techniques for intractable epilepsies associated with unilateral hemispheric pathologies. The authors aimed to investigate possible differences in seizure outcome and complication rates between patients who underwent LPH and VPH. METHODS A comprehensive literature search of PubMed and Embase identified English-language articles published from database inception to December 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…Although complication data, not reported in the recent large multicentric study, 21 are critical for weighing the potential benefit of the different hemispherotomy techniques against their associated risks, overall major complication rates did not differ significantly between hemispherotomy techniques in our study, although hydrocephalus occurred more often in the vertical hemispherotomy cohort. This observation is in line with previous cohort studies 3,5,7,13,42,43 and a recent meta-analysis 18 suggesting comparable overall rates of major surgical complications in vertical vs lateral hemispherotomy cohorts. Our findings thus corroborate that the vertical and lateral hemispherotomy techniques are similarly effective for seizure control, with acceptable and comparable safety profiles, when performed by skilled epilepsy neurosurgeons.…”
Section: Comparing Hemispherotomy Techniquessupporting
confidence: 92%
See 2 more Smart Citations
“…Although complication data, not reported in the recent large multicentric study, 21 are critical for weighing the potential benefit of the different hemispherotomy techniques against their associated risks, overall major complication rates did not differ significantly between hemispherotomy techniques in our study, although hydrocephalus occurred more often in the vertical hemispherotomy cohort. This observation is in line with previous cohort studies 3,5,7,13,42,43 and a recent meta-analysis 18 suggesting comparable overall rates of major surgical complications in vertical vs lateral hemispherotomy cohorts. Our findings thus corroborate that the vertical and lateral hemispherotomy techniques are similarly effective for seizure control, with acceptable and comparable safety profiles, when performed by skilled epilepsy neurosurgeons.…”
Section: Comparing Hemispherotomy Techniquessupporting
confidence: 92%
“…However, because each center commonly uses only one approach, these techniques have not been compared regarding their efficacy and morbidity until recently. In contrast to the findings of a multicentric Italian study 17 and four consecutive meta-analyses, 10,[18][19][20] a recent multicentric international study 21 reported shorter time-to-seizure recurrence and increased seizure recurrence odds for lateral compared to vertical hemispherotomy, fueling an ongoing debate on the impact of surgical techniques on seizure outcomes. The findings of that We found no evidence of an impact of the hemispherotomy technique on seizure outcome (the BF for a model including the hemispherotomy technique over the null model was 1.1), with comparable overall major complication rates for different approaches.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hemispheric disconnections are "radical" procedures for unilateral pathologies. They are associated with a very good seizure prognosis (Engel I in around 80%), although one must accept the expected consequences of these interventions (overview in [10]). Only individual cases of patients aged over 50 years are found here (e.g., [38]), indicating that a meaningful statement about this age group is not possible.…”
Section: Disconnection Proceduresmentioning
confidence: 99%
“…Hemispherotomy is highly effective in suppressing seizures in intractable epilepsy, with extensive epileptogenic regions in the unilateral cerebral hemisphere. 1 ) In addition, it is expected to contribute to growth and brain development by protecting the contralateral cerebral hemisphere. 2 ) In theory, hemispherotomy involves complete disconnection of neural fibers from the contralateral cerebral hemisphere and ipsilateral basal ganglia/thalamus.…”
Section: Introductionmentioning
confidence: 99%